Network Building with the Cytoscape BioGateway App Explained in Five Use Cases. Issue 1 (28th September 2020) - Puig, Rafael Riudavets; Holmås, Stian; Mironov, Vladimir; Kuiper, Martin
Abstract: The BioGateway App is a plugin for the Cytoscape network editor, allowing users to interactively build biological networks by querying the Biogateway Resource Description Framework (RDF) triple store. BioGateway contains information from several curated resources including UniProtKB, IntAct, Gene Ontology Annotations, various datasets containing transcription‐factor regulatory relations to specific target genes, and more. The BioGateway App facilitates the step‐by‐step creation of complex SPARQL queries through an intuitive Graphical User Interface, allowing users to build and explore biological interaction networks to assess, among other things, gene regulatory relationships, gene ontology annotations, and protein‐protein interactions. As the BioGateway information content is most abundant for human proteins and genes, this article describes the utility of the tool through a series of use cases on these human data, starting from the most basic levels and then detailing applications that address some of the rich complexity of the integrated data. Network refinement and display can be further optimized via the selection and filtering possibilities that the Cytoscape framework provides. The use cases also provide examples to explore network information in other species, as they become supported by BioGateway. © 2020 The Authors. Basic Protocol 1 : Introducing a node from the canvas Basic Protocol 2 : Introducing a node from the query builder Basic Protocol 3 : Exploring molecular relationships between diseases Basic Protocol 4 : Find proteins with protein kinase activity involved in a disease and explore the context around them Basic Protocol 5 : Exploring the potential downstream effects after targeted inhibition of proteins Support Protocol : Installation of the BioGateway plugin through the Cytoscape App Manager and from source